‘Repeat testing without having ‘the talk’ is not meaningful’—healthcare providers’ perceptions on finding a balance between Chlamydia trachomatis testing and primary prevention strategies. A qualitative study in Stockholm, Sweden - Ayesha De Costa; Jens Boman; Anna Nielsen; M Salazar (BMJ Open)
Objectives Chlamydia trachomatis is a public health problem. Widespread testing and re-testing after a sexually transmitted infection (STI) is recommended to contain the epidemic and has been adopted by many countries. A recent study in Stockholm found that serial testing was used as a substitute for condom use by youth presenting at the Youth Health Clinics (YHC). The objectives of this study are to explore frontline healthcare provider’s perception of youth testing repeatedly for C. trachomatis as a substitute for condom use and their views on how this might be addressed.Design Qualitative study, in-depth interviews and analysed using content analysis.Setting YHC in Stockholm County, Sweden.Participants Healthcare providers (HCPs) working at the YHC.Findings Testing used as a method of prevention of STIs by youth has been a well-known phenomenon observed by HCPs at the YHC. Despite frustration regarding this behaviour, attitudes towards youth visiting the clinics repeatedly were overall positive. It is seen as an opportunity to reach youth with primary prevention strategies. Time for in-depth conversations with the youth is considered essential to understand the various reasons behind sexual risk-taking and to tailor counselling accordingly. Introducing concepts of self-compassion and self-respect in relation to sex is thought of as an effective intervention to improve sexual health among youth.Conclusion HCPs’ views on testing repeatedly for C. trachomatis as means of prevention, range widely from seeing this as ‘a positive strategy for C. trachomatis prevention’ to ‘a waste of healthcare resources’. There was a more unified view on how this should be addressed. Testing without having time to problematise sexual risk-taking was seen as meaningless. In depth, one-on-one counselling was deemed important. While scaling up accessibility to testing services, primary prevention strategies must not be neglected.